Primary rectal melanoma - a case report (Faculty of Medicine Universitas Indonesia, 2014)
The most common site for malignant melanoma is skin, then eye and third is anorectal region. Primary anorectal malignant melanoma is still very uncommon. It is usually very aggressive and presents with altered bowel habit and rectal bleeding. Proctoscopy shows non-pigmented or lightly pigmented polypoid lesion. Histopathology is confirmatory. Early radical excision is mandatory. A 56 year-old female was presented with malignant melanoma of the lower third of rectum. We report this case for its rarity.